The Influence of Compensation and Working Environment on Employee Performance (Case Study of Mr. Samsudin’s Home Industry) - Agustin Windianingsih; Ratih Ayu Sekarini; Muhammad Iqbal Yusri; Tuhfatul Ibnu Kamal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research seeks to examine how pay and workplace conditions affect workers' productivity in Mr. Samsudin's industry. Using a forty-person sample, the data gathering method in this research is by means of documentation studies, interviews and distributing questionnaires. Data analysis methods make use of the coefficient of determination, t test, f test, and multiple linear regression. For data processing in this study, SPSS for Windows is used. The study's findings indicate that there is a noteworthy and favorable correlation between employee performance and compensation. in Mr. Samsudin's home industry, while Employee performance is negatively and negligibly impacted by the work environment in Mr. Samsudin's home industry. Simultaneously, it shows that there is a significant influence between compensation and the employee environment in Mr. Samsudin's home industry